2014
DOI: 10.1161/circep.113.000799
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Epicardial Ganglionated Plexi Increases Atrial Vulnerability to Arrhythmias in Dogs

Abstract: Background-Previous studies have suggested that systematic ablation of ganglionated plexi (GP) could increase the shortterm success rate of radiofrequency ablation for atrial fibrillation, but the long-term efficacy of this approach is not fully established. Methods and Results-Twenty-four mongrel dogs were divided into 3 groups: epicardial GP ablation group 1 (n=8), epicardial GP ablation group 2 (n=8), and a sham operation group (n=8). In the 2 epicardial GP ablation groups, the 4 major GP and the ligament o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…Moreover, nerve density of parasympathetic and sympathetic nerves was markedly increased after GP ablation. These findings essentially confirm previous experimental studies by Oh et al, 3 Sakamoto et al, 4 and Mao et al 5 all of whom ablated GP, and found evidence of reinnervation providing a reversal of AERP shortening and restoration of atrial fibrillation (AF) inducibility.…”
supporting
confidence: 90%
“…Moreover, nerve density of parasympathetic and sympathetic nerves was markedly increased after GP ablation. These findings essentially confirm previous experimental studies by Oh et al, 3 Sakamoto et al, 4 and Mao et al 5 all of whom ablated GP, and found evidence of reinnervation providing a reversal of AERP shortening and restoration of atrial fibrillation (AF) inducibility.…”
supporting
confidence: 90%
“…81 Autonomic signals to the heart via GP exert important electrophysiological effects including altering atrial refractory periods, 81,82 increasing the frequency of triggered atrial premature beats that can subsequently initiate AF, 83 and increasing the vulnerability of atrial tissue to the induction of AF. 81,84,85 Animal studies have demonstrated that stimulation of GP located around the pulmonary veins can reduce the number of atrial extrastimuli required to initiate AF, and that neuronal/autonomic blockade with drugs or GP ablation can prevent AF induction. 86,87 Because GP are located near the pulmonary veins, conventional PVI can often coincidently eliminate these areas, and it has been suggested that ablation of GP may help explain the success of PVI.…”
Section: The Influence Of the Autonomic Nervous System And Ganglionatmentioning
confidence: 99%
“…They proposed that the acute effect of a ganglionic blocker that is known to manifest hypotension acutely, in the chronic setting could result from increased vasomotor activity via a feedback mechanism or reflex loop. In the study by Mao et al, 23 the paradoxical difference between the acute and the chronic findings for atrial refractoriness and AF inducibility might reside in a similar feedback loop involving a loss of the afferent input from the GP to the vasomotor centers in the brain. During a period of time those medullary nuclei, in response to the decreased neural traffic, adjust by increasing sympathetic and parasympathetic outflow back to the intact atrial neural network.…”
Section: Scherlag and Jackman Paradoxical Effects Of Ganglia Ablationmentioning
confidence: 94%
“…In this issue of the journal, Mao et al 23 have reported another example of the apparently paradoxical interaction between the cardiac autonomic nervous system and AF. In a group of dogs, the major 4 GP and ligament of Marshall were ablated, whereas a comparably sized second group served as sham controls (no GP ablation).…”
Section: Article See P 711mentioning
confidence: 99%